Aspects of healthcare in Ukraine during the German occupation (1941-1944) - Hey, Svitlana (Mos Historicus: A Critical Review of European History, 2023)
The following article examines the Ukrainian healthcare structure during the German occupation. For this purpose, it deploys archival material, contemporary magazines, and newspapers, as well as autobiographical writings, while focusing on the 1941-1943 period. The applied policies were forged both by the aims of the occupational forces and by the acts of local health professionals’ groups. These groups had to face the extreme sanitary circumstances that were created during the war and the occupation. The decline of the former soviet healthcare system was rendering necessary the formation of local healthcare sections and subsections -firstly at prefecture and afterwards at city level- through the so-called local second-grade administration. Additionally, the reoperation of local hospitals was necessitated, even if the available personnel and the resources were limited. The adverse conditions soon forced the German administration to impose new measures whose sole target was the prevention of extended disease propagation to maintain the combat effectiveness of the German troops.